Exploring Pre-service English Teachers' Views on Curriculum Development in a Globalized Society - Ruwaiza Sasmita (STIKes Ibnu Sina Ajibarang, 2026)
Curriculum development has become increasingly important in a globalized society as educational systems are required to respond to cultural changes, technological advancements, global interconnectedness, and emerging competencies. This study aimed to explore pre-service English teachers’ views on curriculum development in a globalized society. Employing a qualitative descriptive research design, this study analyzed pre-service English teachers’ responses through thematic analysis using an established coding framework. The findings revealed four overarching themes: Culture, Technology, Globalization, and 21st Century Skills. These themes demonstrate that participants viewed curriculum development as a multidimensional process involving cultural responsiveness, technological adaptation, global perspectives, and future-oriented competencies. The findings highlight that curriculum development in English Language Education extends beyond the organization of language content and involves consideration of broader learner needs and contemporary educational demands. This study contributes to English Language Education by emphasizing the importance of preparing future teachers who are able to understand and engage with dynamic curriculum development processes. The implications suggest that English teacher education programs and curriculum designers should consider interconnected cultural, technological, global, and twenty-first-century dimensions when developing relevant and responsive English learning curricula.